Metabolic Syndrome– An Ayurvedic Perspective (International Journal of Ayurveda and Pharma Research, 2022)
The prevalence of lifestyle diseases like hypertension, diabetes mellitus, dyslipidemia, and obesity, has been exponentially increasing. Metabolic Syndrome (MS) is a lifestyle disorder that has become a major public-health challenge around the world, owing to rising obesity and sedentary lifestyles. Abdominal obesity, insulin resistance, hypertension, and hyperlipidaemia were the common pathological conditions involved in MS. Ayurveda is the science intended for employing the measures of healthy life. There is no direct reference of metabolic syndrome in Ayurveda classics. Different scholars have different opinion about the nearest possible diseases. Some scholars included it in Medapradooshaja vikaras, while others classified it as Sthoulya upadravas or Avaranajanya vikaras. In Charaka Samhita, lack of physical activity and unhealthy eating habits which are the causes of lifestyle diseases are mentioned in Santharpaneeyam adhyayam. Aetiology and symptomatology of Santharpanajanya vikaras shows a remarkable similarity with metabolic syndrome, since it includes sedentary lifestyle and dietary factors. Therefore, MS can be included under the broad umbrella of Santhartanajanya vikaras and Ayurveda can put forward a better management strategy by reassessing the metabolic syndrome on the basis of Santharpanajanya vikaras